Grenzregionen in Zeiten der Covid-19-Pandemie. Eine Analyse der Berichterstattung der Saarbrücker Zeitung im Frühjahr 2020 - Recktenwald, Katharina; Weber, Florian; Dörrenbächer, H. Peter (2020)
Abstract: „The year 2020 challenged and put into question seeming certainties. The nation states responded to the spread of the coronavirus with varying restrictions of freedom(s), as well as temporary reintroduction of border controls or closures. 35 years after the signing of the Schengen Agreement, the issue of internal border controls within the EU resurfaced – with varying effects on border regions. Buildung upon a constructivistic perspective and based on a qualitative content analysis of newspaper articles of the Saarbrücker Zeitung in spring 2020, the Working Paper traces central discussion processes with a spatial focus on the cross-border area of the Greater Region. Our findings show that reports on securing border crossings outweigh those about reopening borders, underlining the effect of border closings as a sudden rupture with major effects on the lives of border residents, especially cross-border commuters. The actors demand a significant expansion and intensification of cross-border communication and cooperation in response to these experiences.“
Keywords: Berichterstattung; COVID-19; Grenzpolizeiliche Kontrolle; Zeitung

The Neo-Westphalian Public Sphere of Luxembourg. The Rebordering of a Mediated State Democracy in a Cross-Border Context - Lamour, Christian (Tijdschrift voor economische en sociale geografie, 2017)
Abstract: „The mediatised public sphere in Europe seems to be put at risk by the growing importance attached to commercial values in the Media. At the same time, the Westphalian framework of political publicity is said to be diminishing in scale due to globalisation. However, both affirmations are not necessarily true in cross-border metropolitan regions. As suggested in this paper, based on a quantitative and a qualitative analysis of a free daily publication located in the cross-border urban region of Luxembourg, commercial media can help to reconfigure a neo-Westphalian and territorial public sphere made of linear and network-like borders. It is not so much the source of income of the media and the functional dynamics of international urban areas which determine the future of the mediatised public sphere and its territorial background in borderlands Europe but the values of plural reporters in a changing economic and cultural context.“
Keywords: Medien; Medienkonsum; Presse; Zeitung; Öffentlichkeit